Perbandingan Konstitusi Indonesia dan Filipina: Implikasi terhadap Kekuasaan Legislatif di Tingkat Pusat - Intan Riwayaty Amran; Chiquita Chairany (University Of Bengkulu Law Journal, 2024)
This research studies the arrangements in the Indonesian and Philippine constitutions regarding the House of Representatives of both countries. As legislative bodies, both have similar functions but their position in the constitutional structure has significant differences. The comparison between the two legislative bodies is examined in terms of their authority, duties and functions, selection of representatives, composition and relationship with other branches of power. The conclusion of this study found that there are indeed differences in the regulation of legislative power in the Indonesian and Philippine constitutions.